The Effectiveness of Religious-Spiritual Psychotherapy on the Quality of Life of Women with Breast Cancer - F Nasiri (Babol University of Medical Sciences, 2019)
BACKGROUND AND OBJECTIVE: Breast cancer is one of the most common cancers around the world that leads to a decreased quality of life. Since one of the supportive measures is the use of spiritual teachings, the present study was conducted to investigate the effect of religious care on the quality of life of women with breast cancer. METHODS: This quasi-experimental study was conducted in 2017 among women with breast cancer who referred to Qom health centers at least two months after their diagnosis. Seventy subjects were selected through convenience sampling and were randomly assigned to intervention and control groups. For the intervention group, 6 sessions of religious – spiritual psychotherapy were held with the focus of communication with God, other people, self and environment. The quality of life of the subjects was evaluated before the intervention, immediately after the intervention and two months after that using The World Health Organization Quality of Life (WHOQOL) with mean score of 0 – 100. FINDINGS: The results showed a significant difference between the dimensions of quality of life in the control and intervention groups: total health and quality of life (57.61±9.42) vs. (60±19.51) (p=0.002), physical health (46.22±19.53) vs. (61.35±13.36) (p=0.016), mental health (57.85±24.16) vs. (67.55±13.24) (p=0.005), social health (54.88±24.44) vs. (62.79±18.35) (p<0.001), and environmental health (62.05±3.55) vs. (67.33±33.43) (p=0.048), indicating that the results were stable over time. CONCLUSION: The results of the study showed that religious–spiritual psychotherapy increases the quality of life of women with breast cancer.